Reference electrode and manufacturing method thereof

The reference electrode design with a conductive metal/metal salt, water-permeable cellulose, and waterproof insulating layer addresses stability and manufacturing challenges, ensuring stable ion concentration and longevity.

JP2024174507APending Publication Date: 2024-12-17SHIMANE PREFECTURAL GOVERNMENT MATSUE +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023092364
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing reference electrodes face challenges in maintaining stability against changes in chloride ion concentration, longevity, and ease of manufacturing, particularly when using plastic substrates due to high-temperature drying requirements and prolonged manufacturing processes.

Method used

A reference electrode design featuring a conductive metal/metal salt layer, a porous layer with water-permeable cellulose, and a waterproof insulating layer, with an opening for fluid communication, allowing for stable electrolyte supply and ion concentration maintenance.

Benefits of technology

The design provides excellent stability against chloride ion concentration changes, long-term stability, and ease of manufacturing, suitable for disposable applications and electrochemical sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174507000001_ABST
    Figure 2024174507000001_ABST
Patent Text Reader

Abstract

To provide a reference electrode which has excellent stability with respect to a chloride ion concentration change for electrode potential, has excellent aging stability, and is easily manufactured.SOLUTION: A reference electrode includes: a substrate; a conductive metal / metal salt layer formed on the substrate; a porous layer for covering the conductive metal / metal salt layer; and a waterproof insulation layer formed on the porous layer. An opening part for achieving fluid communication between an outside of the reference electrode and the porous layer is formed in the waterproof insulation layer. The porous layer includes an electrolyte and water-permeable cellulose.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reference electrode used in potentiometric measurements and a method for producing the same. [Background technology]

[0002] Usually, the electrode potential in various electrochemical measurements is measured as the potential difference between a reference electrode and an electrode of interest. The latter electrode of interest is called the working electrode, and the former electrode is called the reference electrode. The reaction at the reference electrode is reversible, and it is required that the potential is stable against changes in the composition of the solution to be measured and against the passage of time.

[0003] Representative reference electrodes include the standard hydrogen electrode, the palladium-hydrogen electrode, and the calomel electrode, but the silver / silver chloride (Ag / AgCl) electrode is widely used because it is easy to prepare and use.

[0004] In a conventional silver / silver chloride electrode, a silver / silver chloride electrode is placed inside a support tube with a saturated KCl solution as the internal solution. A liquid junction (generally made of a porous ceramic material) is provided at the tip of the support tube, which maintains an electrical connection with the solution to be measured (also called the sample solution) and prevents the internal solution / measured solution from flowing in or out, thereby keeping the chloride ion concentration substantially constant.

[0005] Furthermore, in recent years, flat-plate reference electrodes, which are easy to fabricate and low cost due to their simple structure and materials, have been widely used, and are particularly suitable for disposable applications. Since they can be fabricated on a flat plate using a printing method, they can be used in sensor chips that can easily perform electrochemical measurements by printing the reference electrode on a single flat plate together with the working electrode and counter electrode. They can also be used as electrodes for chemical sensor chips such as taste sensor chips or biosensor chips. Various attempts have been made to keep the chloride ion concentration constant in such reference electrodes as well.

[0006] For example, Patent Document 1 describes a reference electrode that includes, in combination, a water-impermeable non-conductive substrate having a surface, a conductive metal / metal salt layer disposed on the surface of the substrate, a water-soluble alkali metal salt layer disposed on the surface of the substrate and in contact with at least a portion of the conductive metal / metal salt layer, and a water-impermeable barrier layer that covers a portion of the alkali metal salt layer and a portion of the conductive metal / metal salt layer.

[0007] Furthermore, Patent Document 2 describes a reference electrode in which an electrode layer containing an Ag / AgX salt mixture and a waterproof insulating layer are laminated in this order on an insulating support substrate, in which at least a part of the electrode layer includes a porous electrode region and is provided with an opening for enabling the porous electrode region to be fluidically connected to the outside of the electrode.

[0008] Patent Document 3 describes a reference electrode for a chemical sensory sensor, which has a first conductor, a wetting layer in which an electrolyte capable of charge exchange between the first conductor and the wetting layer is held in a wetting material, a charge exchange prevention layer that prevents the electrolyte held in the wetting layer from exchanging charges with external ions, and an electrolyte leakage prevention layer that prevents the electrolyte held in the wetting layer from leaking to the outside. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US Patent Application Publication No. 2005 / 0191429 [Patent Document 2] JP 2019-20342 A [Patent Document 3] JP 2007-57459 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, in the reference electrode of Patent Document 1, acetophenone (bp: 202°C) and benzyl alcohol (bp: 205.3°C) are used as solvents in the alkali metal salt layer. This reference electrode is thought to require high-temperature drying / vacuum drying to volatilize the solvent, but high-temperature drying requires the use of a substrate that can withstand high temperatures, and plastic substrates, for example, are unsuitable. In addition, polyethylene oxide (PEO) remains in the alkali metal salt layer, which raises concerns about the stability of the reference electrode over time.

[0011] In the reference electrode of Patent Document 2, a porous electrode region is formed by immersion treatment. In Patent Document 2, under certain conditions, overnight immersion may be required to make the Ag / AgCl layer passivate and to contain KCl, which requires a long manufacturing process. In addition, the position where the working electrode is manufactured may be limited due to the immersion of the reference electrode, which is a problem in the manufacturing process. In addition, when the KCl region is formed by a porous precursor electrode region, particularly when the dispersion material of the Ag / AgCl / KCl paste is PEO, high-temperature firing is required, which is particularly unsuitable for plastic substrates.

[0012] In the reference electrode for a chemical sensory sensor of Patent Document 3, the wet layer containing KCl is semi-solid, and therefore there is a concern about the stability of the reference electrode over time.

[0013] As described above, although several reference electrodes have been proposed, there is a need for a further reference electrode which has good stability of the electrode potential against changes in chloride ion concentration, excellent stability over time, and is easy to manufacture. [Means for solving the problem]

[0014] A first example of the means for solving the problems of the present invention is as follows: base material, a conductive metal / metal salt layer formed on said substrate; a porous layer covering said conductive metal / metal salt layer; a waterproof insulating layer formed on the porous layer; A reference electrode having an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; The porous layer is a reference electrode, containing an electrolyte and water-permeable cellulose.

[0015] Alternatively, a second example of the means for solving the problem of the present invention is Providing a substrate; forming a conductive metal / metal salt layer on the substrate; forming a porous layer overlying the conductive metal / metal salt layer; forming a waterproof insulating layer on the porous layer; A method for producing a reference electrode comprising the steps of: an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; A method for producing a reference electrode, wherein the porous layer comprises an electrolyte and water-permeable cellulose.

[0016] Here, the water-permeable cellulose is preferably selected from the group consisting of crystalline cellulose and pulp.

[0017] The water-permeable cellulose preferably accounts for 10 to 90% by weight based on the total weight of the porous layer.

[0018] Furthermore, it is preferable that the porous layer further contains cellulose nanofibers.

[0019] Furthermore, the cellulose nanofibers preferably account for 1 to 90% by weight based on the total weight of the porous layer.

[0020] Furthermore, the conductive metal / metal salt layer is preferably formed from a material selected from the group consisting of Ag / AgCl, Ag / AgBr, Ag / AgI, and Ag / AgSCN.

[0021] Furthermore, the electrolyte is preferably selected from combinations of alkali metals and anions, such as KCl, KBr, KI, KSCN, NaCl, NaBr, NaI, and NaSCN.

[0022] In the second example, it is preferable that the method further includes a step of drying the dispersion liquid for the porous layer to form the porous layer, and the drying is performed at 50 to 90°C.

[0023] Alternatively, a third example of the means for solving the problems of the present invention is a sensor including the reference electrode of the first example. Effect of the Invention

[0024] According to the present invention, it is possible to provide a reference electrode which has good stability of the electrode potential against changes in chloride ion concentration, excellent stability over time, and is easy to manufacture. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a reference electrode according to the present invention. [Diagram 2] FIG. 2 is a schematic plan view showing an example of a reference electrode according to the present invention. [Diagram 3] FIG. 3 is a schematic plan view showing an example of a sensor equipped with a reference electrode according to the present invention. [Figure 4] FIG. 4 shows how water does not penetrate into an aggregate of cellulose nanofibers (CNF). [Diagram 5] FIG. 5 is an image diagram of the water permeation pathway into an aggregate of crystalline cellulose (CC). [Figure 6] FIG. 6 is an image diagram of the water permeation path into the porous layer. [Figure 7] FIG. 7 is a schematic perspective view showing a jig suitable for measuring a small amount used in the test. [Figure 8] FIG. 8 is a graph showing the relationship between the potential of the reference electrode and the elapsed time. [Figure 9] FIG. 9 is a diagram showing the relationship between the potential of the surrounding electrodes and the elapsed time. [Figure 10] FIG. 10 is a graph showing the relationship between the potential of a commercially available reference electrode and the elapsed time for reference. [Figure 11] FIG. 11 is an electron microscope photograph of crystalline cellulose (CC). [Figure 12] Figure 12 is an electron microscope photograph of a dried cellulose nanofiber (CNF) dispersion. [Figure 13] FIG. 13 is an electron microscope photograph of the surface of the porous layer obtained in this example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, examples of embodiments of the present invention will be described with reference to the drawings. Note that the present invention is not limited to the following embodiments, and may be embodied in various different forms without departing from the technical concept of the invention.

[0027] The first embodiment for carrying out the present invention is base material, a conductive metal / metal salt layer formed on said substrate; a porous layer covering said conductive metal / metal salt layer; a waterproof insulating layer formed on the porous layer; A reference electrode having an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; The porous layer is a reference electrode, containing an electrolyte and water-permeable cellulose.

[0028] Fig. 1 is a schematic cross-sectional view showing an example of a reference electrode according to the present invention, and Fig. 2 is a schematic plan view showing an example of a reference electrode according to the present invention.

[0029] As shown in Figures 1 and 2, the reference electrode 10 in this embodiment has a substrate 12, a conductive metal / metal salt layer 14 formed on the substrate 12, a porous layer 16 covering the conductive metal / metal salt layer 14, and a waterproof insulating layer 18 formed on the porous layer 16, and an opening 20 is formed in the waterproof insulating layer 18 to allow fluid communication between the outside of the reference electrode 10 and the porous layer 16, and the porous layer 16 contains an electrolyte and water-permeable cellulose.

[0030] <Reference electrode> Various types of reference electrodes can be widely used. The reference electrode is suitable for disposable use because of its simple structure and material. For example, by printing the reference electrode on a single flat plate together with the working electrode and counter electrode, it can be used as a sensor chip that can easily perform electrochemical measurement. Alternatively, it can be used as an electrode for a chemical sensor chip such as a taste sensor chip or a biosensor chip.

[0031] <Base material> The substrate supports a conductive metal / metal salt layer, which is an electrode layer. The substrate may be an insulator and may be immersed in a solution to be measured (also called a sample liquid) or the like and may provide sufficient strength for measurement. The substrate may be made of any material commonly used in the art, such as glass, plastics such as polyethylene terephthalate film (PET), synthetic rubber, ceramics, or water-resistant paper or wood. The substrate is typically a flat substrate, but may also have other curved shapes. When the substrate is a flat substrate, its typical thickness may be 50 to 2000 μm.

[0032] <Conductive metal / metal salt layer> The conductive metal / metal salt layer functions as an electrode layer and is a layer containing a conductive metal and a metal salt. The conductive metal in the conductive metal / metal salt layer may be, but is not limited to, a metal such as aluminum, chromium, copper, silver, platinum, gold, or carbon. The conductive metal in the conductive metal / metal salt layer is preferably silver. The metal constituting the metal salt in the conductive metal / metal salt layer may be, but is not limited to, a metal such as aluminum, chromium, copper, silver, platinum, gold, or carbon. The metal constituting the metal salt in the conductive metal / metal salt layer is preferably silver. The salt constituting the metal salt in the conductive metal / metal salt layer is preferably Cl. - , Br - , I - or SCN - The metal salt in the conductive metal / metal salt layer may be, but is not limited to, Cl. - The conductive metal / metal salt layer is preferably a silver / silver chloride (Ag / AgCl) layer.

[0033] To form the conductive metal / metal salt layer, for example, a conductive metal / metal salt paste can be used. From the viewpoints of potential stability and electrical resistance, the weight ratio of the conductive metal to the metal salt in the paste is preferably 95:5 to 5:95, and more preferably 90:10 to 20:80.

[0034] A water-soluble dispersant such as polyethylene glycol may be added to the conductive metal / metal salt paste. This addition allows for smoother printing. The water-soluble dispersant only needs to be added in a necessary and sufficient amount to facilitate application of the paste, but it is preferable to remove it from the electrode layer by vaporization and decomposition by heating and drying after application.

[0035] The thickness of the conductive metal / metal salt layer can be preferably set to 0.1 to 200 μm from the viewpoint of the permeability of the solution to be measured.

[0036] <Porous layer> The porous layer is a layer that covers the conductive metal / metal salt layer. In this embodiment, the porous layer contains an electrolyte and water-permeable cellulose.

[0037] The porous layer typically acts as a member equivalent to the liquid junction of a conventional silver / silver chloride internal electrode (fluid communication control function). When the reference electrode is brought into contact with the solution to be measured, the electrolyte contained in the porous layer forms an aqueous electrolyte solution (preferably a saturated aqueous solution) as the internal solution.

[0038] The porous layer is typically a layer having a structure with voids that can be obtained by removing water from water-permeable cellulose by heating, drying, etc. The porous layer can also be formed from crystal voids formed by dissolving an electrolyte such as KCl in the presence of water-permeable cellulose and then drying. Note that some water may remain in the porous layer.

[0039] <Electrolytes> An electrolyte consists of positive metal ions and negative ions. Metal ions are, for example, alkali metal ions or alkaline earth metal ions, such as K and Na. Negative ions are, for example, Cl. - , Br - , I - and SCN - and preferably Cl - ions. Preferably, the electrolyte is selected from a combination of an alkali metal and an anion, such as KCl, KBr, KI, KSCN, NaCl, NaBr, NaI, or NaSCN. Of these electrolytes, KCl is most preferred because the transport numbers of the cations and anions are almost equal. An aqueous solution of such an electrolyte serves as a source for stably supplying negative ions to the electrode surface during potential measurement. The content of the electrolyte is preferably equal to or greater than the solubility at room temperature in water equivalent to the volume of the pores in the porous layer.

[0040] Preferably, the electrolyte is 10 to 90% by weight based on the total weight of the porous layer. If the electrolyte is 10% by weight or more, it is preferable for forming a saturated electrolyte solution in the porous layer, and if it is 90% by weight or less, it is preferable for the subsequent process of printing a waterproof insulating layer and for suppressing the diffusion of the electrolyte dissolved by immersion in water during measurement. More preferably, the electrolyte is 20 to 60% by weight based on the total weight of the porous layer. The amount of the electrolyte is appropriately determined in relation to the amount of water-permeable cellulose.

[0041] When the reference electrode is brought into contact with the solution to be measured, an aqueous electrolyte solution is rapidly formed in the porous layer using the water of the solution to be measured as a medium. That is, water enters the gaps in the structure of the porous layer and dissolves the electrolyte, thereby rapidly forming an aqueous electrolyte solution. Since a large amount of electrolyte is present, the aqueous electrolyte solution in the porous layer is in a supersaturated, saturated, or nearly saturated state, which contributes to stabilization of the potential.

[0042] <Water-permeable cellulose> Water-permeable cellulose is cellulose that has the property of being able to penetrate water by capillary action. In the present application, "water-permeable" refers to cellulose having the property of allowing water to pass through. Any cellulose having the above-mentioned properties can be used as the water-permeable cellulose, but it is preferable to use, for example, crystalline cellulose, pulp, etc. In addition, when using pulp, it is preferable to use any further additive in order to obtain uniform dispersibility of the solution in the dispersion liquid for the porous layer.

[0043] The fiber diameter and particle diameter of the water-permeable cellulose are not particularly limited as long as the cellulose has the above-mentioned properties. Whether the cellulose is water-permeable or not may depend on, for example, the size of the cellulose. For example, non-water-permeable cellulose (CNF) has thin fibers and very narrow gaps between the fibers, making it difficult (impossible or time-consuming) to allow water to pass through (see FIG. 4), but if the cellulose fibers have a certain fiber diameter (e.g., 100 nm or more, not shown) or the cellulose particles have a certain particle diameter (e.g., 100 nm or more, see FIG. 5), gaps will form between the fibers and between the particles, allowing water to pass through. For example, the water-permeable cellulose may contain at least 50% cellulose with a fiber diameter of 100 nm or more (assuming pulp). In this case, the fiber diameter can be measured, for example, by observation with an electron microscope. Alternatively, for example, the water-permeable cellulose may contain at least 50% cellulose with a particle diameter of 100 nm or more (assuming crystalline cellulose). In this case, the particle diameter is, for example, the mode diameter. The length of the water-permeable cellulose fibers is preferably 1 to 1000 μm, more preferably 1 to 500 μm. The water-permeable cellulose has pores of approximately the same diameter even after drying.

[0044] Preferably, the water-permeable cellulose is 10 to 90% by weight based on the total weight of the porous layer. If the water-permeable cellulose is 10% by weight or more, the amount of electrolyte added can be relatively reduced, so that the amount of electrolyte diffusion during measurement is reduced and there is no effect on the surrounding electrodes, which is preferable. If the water-permeable cellulose is 90% by weight or less, the amount of electrolyte added relatively increases, so that it becomes easier to form a saturated electrolyte solution when immersed in water, and it becomes easier to maintain the concentration, which is preferable. More preferably, the water-permeable cellulose is 30 to 70% by weight based on the total weight of the porous layer.

[0045] <Crystalline Cellulose> Preferably, the water-permeable cellulose is crystalline cellulose (CC). Crystalline cellulose is an aggregate (secondary and tertiary particles) of cellulose nanocrystals. The characteristics of crystalline cellulose include water permeability (capillary structure) and the ability to suppress the amount of electrolyte (KCl) (suppression of outflow). In this application, an aggregate of 30 to 40 cellulose molecular chains is called a microfibril, an aggregate of these is called a cellulose nanofiber (CNF), a short cellulose nanofiber is called a cellulose nanocrystal, a secondary particle or tertiary particle of an aggregate of cellulose nanocrystals is called a crystalline cellulose, and a material assembled from the above that does not return to its original state is called pulp. For reference, Table 1, which classifies nanocellulose by size, is shown below.

[0046] [Table 1]

[0047] <Waterproof insulating layer> A waterproof insulating layer is formed on the porous layer. The waterproof insulating layer is a waterproof layer having an insulating function. The waterproof insulating layer restricts the fluid communication between the porous layer and the external solution, and contributes to stabilizing the negative ion concentration on the surface of the conductive metal / metal salt layer. The waterproof insulating layer allows fluid communication between the outside of the reference electrode and the porous layer through an opening, which will be described later. Preferably, if the waterproof insulating layer, except for the opening, completely covers the porous layer, it is possible to prevent the components in the porous layer from leaking out from other than the opening, and to avoid the adverse effect of the electrolyte on the surrounding electrodes.

[0048] Any conventionally known waterproof material can be used as a suitable material for forming the waterproof insulating layer. As the waterproof insulating layer, plastics such as polyvinyl chloride, polyvinylidene chloride, polystyrene, polyurethane, polysulfone, polycarbonate, polyarylate, polyamide, polyvinyl alcohol, and synthetic resins such as acrylic resin, epoxy resin, urethane resin, phenol resin, and melamine resin can be used. The waterproof insulating layer may be an energy ray curable resin or a thermosetting resin curable by energy rays such as ultraviolet rays.

[0049] <Opening> An opening is formed in the waterproof insulating layer to allow fluid communication between the exterior of the reference electrode and the porous layer.

[0050] An opening can be provided in the waterproof insulating layer to expose a part of the porous layer to the outside through the opening. Such an opening can be provided in the center of the waterproof insulating layer or on the side of the conductive metal / metal salt layer (the peripheral end of the conductive metal / metal salt layer). In an embodiment in which an opening is provided on the side of the conductive metal / metal salt layer, for example, the porous layer can be formed by reaching the side of the reference electrode and not covering at least a part of this side with the waterproof insulating layer or the like.

[0051] The size of the opening can be selected appropriately so that the solution to be measured can quickly enter the porous layer and quickly become measurable. From this point of view, the planar shape of the opening may be any shape, but it is preferable that the opening has an equivalent circle diameter of at least 0.1 mm. Here, the equivalent circle diameter refers to the diameter of a perfect circle having an area equivalent to the planar area of ​​the opening.

[0052] The fluid communication of the solution to be measured between the outside of the reference electrode and the porous layer through the opening is sufficient to maintain electrical connection, while only a small amount of the internal solution in the porous layer flows out, allowing the concentration of negative ions (typically chloride ions) on the electrode surface to be kept substantially constant for a sufficient period of time required for measurement.

[0053] <Water-impermeable cellulose> Optionally, the porous layer further comprises water-impermeable cellulose. In the present application, "water-impermeable" refers to cellulose not having the property of allowing water to pass through. Water-impermeable cellulose is cellulose that does not allow water to penetrate due to capillary action. In other words, water-impermeable cellulose is cellulose that does not have gaps through which water can penetrate due to extremely fine fibers. Water-impermeable cellulose includes cellulose particles preferably having a length of less than 1 μm. Any cellulose having the above properties can be used as the water-impermeable cellulose, but cellulose nanofibers (CNF) can be preferably used.

[0054] <Cellulose nanofiber> Optionally, the porous layer further contains cellulose nanofibers (CNF) as water-impermeable cellulose. Cellulose nanofibers refer to plant fibers mechanically defibrated to nano-size (diameter of several to several tens of nanometers). The cellulose nanofibers in the present application include various forms. For example, the cellulose nanofibers can be cellulose microfibrils (single nanofibers) consisting of crystalline, quasi-crystalline, and amorphous parts, or aggregates thereof having a longitudinally torn, tangled, or mesh-like structure, and preferably have a width of 3 to 100 nm, an aspect ratio of 10 or more, and a length of up to 100 μm.

[0055] Preferably, the cellulose nanofibers are 1 to 80% by weight based on the total weight of the porous layer. If the cellulose nanofibers are 1% by weight or more, this is preferable for suppressing crystal growth of the electrolyte during drying of the dispersion liquid for the porous layer and for assisting dispersion of crystalline cellulose in the dispersion liquid for the porous layer, while if the cellulose nanofibers are 80% by weight or less, this is preferable for improving the water permeability of the measurement solution. More preferably, the cellulose nanofibers are 1 to 30% by weight based on the total weight of the porous layer.

[0056] The functions of CNF include no water penetration, aiding in the dispersion of crystalline cellulose, and controlling the crystal growth of electrolytes. Therefore, a dispersion of CNF can be added to improve the water dispersibility of the dispersion for the porous layer and to suppress the crystal growth of electrolyte (KCl) during drying. By adding CNF, it is possible to disperse crystalline cellulose (water-permeable cellulose) more uniformly in the dispersion for the porous layer. In addition, by adding CNF, it is possible to suppress unevenness (which has a negative effect on insulating layer printing) caused by the crystal growth of electrolyte (KCl) during drying.

[0057] FIG. 6 is an image of the water permeation path into the porous layer. Reference number 1 indicates that water permeates between particles of water-permeable cellulose (crystalline cellulose (CC)) due to capillary action. Reference number 2 indicates that water permeates into voids formed by dissolving an electrolyte (typically KCl). Considering the time scale (fast) for water permeation, it is considered that water permeates more through the flow paths between particles of crystalline cellulose (several tens of μm particles) (than through voids in CC). In addition, when the dispersion liquid for the porous layer containing CNF is dried, the crystal growth of KCl is suppressed and the KCl crystals become less uneven, making the subsequent process of printing the insulating layer easier.

[0058] <Method of manufacturing the reference electrode> A second embodiment for carrying out the present invention is Providing a substrate; forming a conductive metal / metal salt layer on the substrate; forming a porous layer overlying the conductive metal / metal salt layer; forming a waterproof insulating layer on the porous layer; A method for producing a reference electrode comprising the steps of: an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; A method for producing a reference electrode, wherein the porous layer comprises an electrolyte and water-permeable cellulose.

[0059] In explaining the method for manufacturing a reference electrode of the second embodiment for carrying out the present invention, the explanation of the components of the reference electrode of the first embodiment can be used as appropriate, so further explanation of the overlapping components will be omitted.

[0060] In the step of preparing a substrate, the substrate described above is appropriately prepared.

[0061] In the step of forming a conductive metal / metal salt layer on a substrate, the conductive metal / metal salt layer can be formed on the substrate by a method generally used in the field. For example, a conductive metal / metal salt paste can be applied to the substrate by screen printing or the like, and then dried to form a conductive metal / metal salt layer on the substrate. The conductive metal / metal salt layer may also be formed by sputtering or vapor deposition. Preferably, the conductive metal / metal salt layer can be easily produced by using a printing technique.

[0062] In the step of forming a porous layer covering the conductive metal / metal salt layer, the porous layer can be formed by a dropping method, specifically, automatic dropping using an automatic dispenser.

[0063] To form a porous layer, for example, a dispersion liquid for a porous layer containing an electrolyte, water-permeable cellulose, water, and ethanol is first prepared. Based on the total weight of the dispersion liquid for a porous layer, the electrolyte is preferably 1 to 10% by weight, the water-permeable cellulose is preferably 1 to 10% by weight, the water is preferably 50 to 90% by weight, and the ethanol is preferably 0 to 20% by weight.

[0064] The prepared dispersion liquid for the porous layer can be dropped onto the conductive metal / metal salt layer on the substrate by a dropping method. It is also possible to prepare a porous layer by applying the dispersion liquid for the porous layer using a printing method or the like and drying it.

[0065] The dispersion liquid for the porous layer is preferably dried at 50 to 90°C. A temperature of 50°C or higher is preferable because it suppresses crystal growth of the electrolyte, and a temperature of 90°C or lower is preferable because it suppresses deviation due to boiling. Usually, heating at a temperature of about 50 to 90°C for about 30 minutes to 1 hour is sufficient. This makes it possible to remove water contained in the dispersion liquid for the porous layer.

[0066] In the step of forming the waterproof insulating layer on the porous layer, an energy ray curable resin protective layer material may be screen-printed on the porous layer and exposed to light to form the waterproof insulating layer.

[0067] The openings can be easily formed by, for example, forming a printing pattern of the waterproof insulating layer in advance so that the openings are formed at the same time, which is preferable from the viewpoint of stable production. Alternatively, the openings may be formed by removing a part of the waterproof insulating layer.

[0068] As a result of extensive research by the present inventors, it has been found that by forming water-permeable cellulose together with an electrolyte as a porous layer and supporting this porous layer with a waterproof insulating layer, pores are formed and maintained between the particles of the water-permeable cellulose and the particles of the electrolyte, thereby forming a reference electrode in which the outflow of electrolyte is also controlled. EXAMPLES

[0069] An embodiment of the present invention will now be described. In this embodiment, a sensor 22 equipped with a reference electrode A shown in Fig. 3 was produced. Fig. 3 is a schematic plan view showing an example of a sensor equipped with a reference electrode according to the present invention. In Fig. 3, the sensor 22 is provided with a reference electrode A and a surrounding electrode B.

[0070] <Manufacture of reference electrode> Ag / AgCl paste (manufactured by BAS Co., Ltd., weight ratio 30-50:15-25) was printed in the pattern shown in Figure 3 on a substrate (Toray Lumirror film, 250 μm thick, flat substrate of approximately 100 mm x 150 mm) and dried in an oven at 150°C for 16 hours to form an Ag / AgCl layer. The thickness of the Ag / AgCl layer was approximately 10-50 μm. A screen printer MT-320TV manufactured by Microtec Co., Ltd. was used for printing.

[0071] Next, a porous layer was formed by the dropping method. As the dispersion for the porous layer, a mixture of 4g of cellulose nanofiber BiNFis WMa-10002, 0.5g of Cellulose microcrystalline powder (crystalline cellulose, diameter 1-50μm, length 10-200μm), 0.4g of KCl (electrolyte), 4g of water, and 1g of ethanol was used. The blending ratio of the dispersion for the porous layer is shown in Table 2.

[0072] [Table 2]

[0073] The dispersion liquid for the porous layer was dropped onto the Ag / AgCl layer by a dropping method, and then dried in an oven at 80° C. for 40 minutes.

[0074] Next, a waterproof insulating layer was printed using a UV-curable solder resist (manufactured by GOO Chemical Industry Co., Ltd.) and cured by UV irradiation. The thickness of the waterproof insulating layer was about 20 to 80 μm. Here, the diameter of the opening was 1 mm.

[0075] The peripheral electrodes were prepared for the purpose of checking the elution, but a detailed description thereof will be omitted.

[0076] The potential of the obtained reference electrode was measured. For the test, a jig suitable for small amount measurement shown in FIG. 7 was used. FIG. 7 is a schematic perspective view showing the jig suitable for small amount measurement used for the test. Specifically, the sensor in FIG. 3 was tested in the jig in FIG. 7 using a commercially available glass reference electrode as the standard electrode.

[0077] The test results are shown in Figures 8 and 9. Figure 8 is a graph showing the relationship between the potential of the reference electrode and the elapsed time. Figure 9 is a graph showing the relationship between the potential of the surrounding electrode and the elapsed time. Note that the potential of a commercially available reference electrode is shown in Figure 10 for reference. Figure 10 is a graph showing the relationship between the potential of a commercially available reference electrode and the elapsed time for reference.

[0078] As shown in FIG. 8, regardless of the environment of the measurement solution (3 mM KCl), a potential equivalent to that of a saturated KCl solution (a potential equivalent to that of a commercially available glass reference electrode) was obtained.

[0079] We also investigated the potential of the surrounding electrodes (Ag / AgCl) (Figure 9). There was no effect of (dissolved) KCl on the surrounding electrodes.

[0080] Figure 11 is an electron microscope photograph of crystalline cellulose (CC). Figure 12 is an electron microscope photograph of a dried product of a cellulose nanofiber (CNF) dispersion. Figure 13 is an electron microscope photograph of the surface of the porous layer obtained in this example. As shown in Figure 13, it can be seen that the cellulose nanofibers cover the electrolyte KCl, suppressing the crystal growth of KCl.

[0081] In this example, cellulose nanofibers are used in forming the porous layer, but the reference electrode may be made using crystalline cellulose and an electrolyte without using cellulose nanofibers.

[0082] The present invention is not limited to the configurations of the embodiments shown in the drawings. The ranges of individual values ​​and conditions of the embodiments can be appropriately changed and modified within the scope of the technical concept of the present invention. [Explanation of symbols]

[0083] 10, A reference electrode 12 Base material 14 Conductive metal / metal salt layer 16 Porous layer 18 Waterproof insulating layer 20 Opening 22 Sensors B Surrounding electrode

Claims

1. base material, a conductive metal / metal salt layer formed on said substrate; a porous layer covering said conductive metal / metal salt layer; a waterproof insulating layer formed on the porous layer; A reference electrode having an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; A reference electrode, wherein the porous layer comprises an electrolyte and water-permeable cellulose.

2. 2. The reference electrode of claim 1, wherein the water-permeable cellulose is selected from the group consisting of crystalline cellulose and pulp.

3. 2. The reference electrode according to claim 1, wherein the water-permeable cellulose is 10 to 90% by weight, based on the total weight of the porous layer.

4. 2. The reference electrode of claim 1, wherein the porous layer further comprises cellulose nanofibers.

5. The reference electrode according to claim 4, wherein the cellulose nanofibers are present in an amount of 1 to 80% by weight, based on the total weight of the porous layer.

6. 2. The reference electrode of claim 1, wherein the conductive metal / metal salt layer is formed from a material selected from the group consisting of Ag / AgCl, Ag / AgBr, Ag / AgI, Ag / AgSCN.

7. 2. The reference electrode of claim 1, wherein the electrolyte is selected from the group consisting of KCl, KBr, KI, KSCN, NaCl, NaBr, NaI, and NaSCN.

8. A sensor comprising the reference electrode according to any one of claims 1 to 7.

9. Providing a substrate; forming a conductive metal / metal salt layer on the substrate; forming a porous layer overlying the conductive metal / metal salt layer; forming a waterproof insulating layer on the porous layer; A method for producing a reference electrode comprising the steps of: an opening is formed in the waterproof insulating layer to allow fluid communication between an exterior of the reference electrode and the porous layer; The method for producing a reference electrode, wherein the porous layer comprises an electrolyte and water-permeable cellulose.

10. The method according to claim 9, wherein the water-permeable cellulose is selected from the group consisting of crystalline cellulose and pulp.

11. The method according to claim 9, wherein the water-permeable cellulose is 10 to 90% by weight, based on the total weight of the porous layer.

12. The method of claim 9 , wherein the porous layer further comprises cellulose nanofibers.

13. The method according to claim 12, wherein the cellulose nanofibers are present in an amount of 1 to 80% by weight based on the total weight of the porous layer.

14. The method of claim 9, wherein the conductive metal / metal salt layer is formed from a material selected from the group consisting of Ag / AgCl, Ag / AgBr, Ag / AgI, Ag / AgSCN.

15. 10. The method of claim 9, wherein the electrolyte is selected from the group consisting of KCl, KBr, KI, KSCN, NaCl, NaBr, NaI, and NaSCN.

16. The method according to claim 9, further comprising the step of drying the dispersion for the porous layer to form the porous layer, wherein the drying is carried out at 50 to 90°C.

Citation Information

Patent Citations

  • Chemical sensing capacity sensor chip

    JP2007057459A

  • Flat reference electrode and manufacturing method therefor

    JP2019020342A

  • Reference electrode

    US20050191429A1